Malrotation Induced Small Intestine Ischemia in an Adolescent - Karadeniz Erdem; Atamanalp Selçuk Sabri (Case Reports in Surgery)
Intestinal malrotation occurs if midgut does not complete or partially completes its 270° counter-clockwise rotation around the superior mesenteric artery during embryologic life. In general, it frequently manifests with vomiting due to duodenal obstruction and volvulus in the initial months of life, and it is very rare to manifest in the adulthood. A 20-year-old male patient who had severe abdominal pain, nausea, vomiting, and distention for one day was evaluated at the emergency department. On abdominal tomography “swirling appearance of structures around the superior mesenteric artery” was reported. CT appearance was considered compatible with a rotational anomaly. Emergency surgery was planned for the patient. In laparotomy, it was observed that an approximately 100 cm long small intestine segment was rotated around a band (Ladd) and ischemia was developed in this segment due to rotation of its mesentery. The rotation of the small intestinal mesentery was corrected by opening the bands. After the warm application to the intestinal mesenteric ischemia for a while, the color and the peristalsis of the intestines became normal. The patient was discharged on postoperative day 2 with suggestions.